De NovoSCN8A Mutation Identified by Whole-Exome Sequencing in a Boy With Neonatal Epileptic Encephalopathy, Multiple Congenital Anomalies, and Movement Disorders. (December 2014) - Vaher, Ulvi; Nõukas, Margit; Nikopensius, Tiit; Kals, Mart; Annilo, Tarmo; Nelis, Mari; Õunap, Katrin; Reimand, Tiia; Talvik, Inga; Ilves, Pilvi; Piirsoo, Andres; Seppet, Enn; et al.
Epileptic encephalopathies represent a clinically and genetically heterogeneous group of disorders, majority of which are of unknown etiology. We used whole-exome sequencing of a parent-offspring trio to identify the cause of early infantile epileptic encephalopathy in a boy with neonatal seizures, movement disorders, and multiple congenital anomalies who died at the age of 17 months because of respiratory illness and identified a de novo heterozygous missense mutation (c.3979A>G; p.Ile1327Val) in SCN8A (voltage-gated sodium-channel type VIII alpha subunit) gene. The variant was confirmed in the proband with Sanger sequencing. Because the clinical phenotype associated with SCN8A mutations has previously been identified only in a few patients with or without epileptic seizures, these data together with our results suggest that mutations in SCN8A can lead to early infantile epileptic encephalopathy with a broad phenotypic spectrum. Additional investigations will be worthwhile to determine the prevalence and contribution of SCN8A mutations to epileptic encephalopathies.